2013
DOI: 10.1123/rsj.37.2.147
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Social Media Marketing: The Impact of Facebook Status Updates on a Campus Recreation Event

Abstract: Social media marketing, including the use of Facebook, is becoming a prevalent part of the promotional marketing mix by recreation and sport organizations. While use of Facebook as a marketing tool is common, empirical evidence of its use is lacking. This study examined the effectiveness of social media marketing on college students in a campus recreation setting. Specifically, the effectiveness of Facebook status messages were assessed via a 2 × 2 repeated factorial within-subjects design to determine their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
(24 reference statements)
2
11
0
1
Order By: Relevance
“…In order to make sure the effectiveness, hoteliers need to pay special attention to finding the right target market with help of big data, to effectively convey effective message with effective format, to manipulate the involvement of Key Opinion Leaders and to realize actual transaction (Bayne & Cianfrone, 2013). Social media marketing is a relatively new subject in the hospitality and marketing field.…”
Section: Measures To Reassure Social Media Marketing Effectivenessmentioning
confidence: 99%
“…In order to make sure the effectiveness, hoteliers need to pay special attention to finding the right target market with help of big data, to effectively convey effective message with effective format, to manipulate the involvement of Key Opinion Leaders and to realize actual transaction (Bayne & Cianfrone, 2013). Social media marketing is a relatively new subject in the hospitality and marketing field.…”
Section: Measures To Reassure Social Media Marketing Effectivenessmentioning
confidence: 99%
“…Focusing marketing on relationship building may be especially successful in the campus recreation setting because centers provide opportunities for students to build social bonds (Miller, 2011). Bayne and Cianfrone (2013) specifically suggested Facebook was a useful tool for campus recreation managers. They advocated for using this medium to encourage student participation at the center.…”
Section: Marketing Social Media and Building Relationshipsmentioning
confidence: 99%
“…While campus recreation programs are using social media such as Facebook and Twitter to promote their facilities and activities (Kaltenbaugh et al, 2011), little research into whether social media marketing in recreation is effective has been conducted. In one study, Bayne and Cianfrone (2013) found that, while students were connected via social media, the advertising messages sent by recreation center staff had little effect on students outside of increasing awareness. However, they suggested the impacts of Facebook awareness alone should encourage recreation facilities to actively increase their number of Facebook fans.…”
Section: Marketing Social Media and Building Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations